Assessing Social Vulnerability to Flood Hazards in the Dutch Province of Zeeland - Kirby, Ryan H.; Reams, Margaret A.; Lam, Nina S. N.; Zou, Lei; Dekker, Gerben G. J.; Fundter, D. Q. P. (International Journal of Disaster Risk Science, 2019)
The 2007 European Union Floods Directive encouraged member nations to pursue a more integrated view of flood risks and management strategies, taking into account social vulnerabilities of residents. To date, most flood-risk analyses conducted by the Dutch government have focused on physical risk. This study utilizes fine-scale data to construct a social vulnerability index for 147 districts of the Dutch province of Zeeland, located in the Southwestern Delta and the scene of widespread devastation following the 1953 North Sea Flood. Factor analysis of 25 indicators of social vulnerability selected from related research in Europe and the United States results in seven factors explaining roughly 66% of the total variance. These factors of social vulnerability in Zeeland are urban density, low-income households, recent population change, female gender, train access, and self-employed and service-sector employment. The index was constructed using the top-loading variable in each of these factors, with weights determined by the variance explained by each factor. Scores range from a low of 0.20 in Schore, municipality of Kapelle, to the highest score of 0.64 in Oudelandse Hoeve of Terneuzen. The most vulnerable districts are located in South Zeeland, with eight of the 10 found in Terneuzen. The majority of less vulnerable districts are located in Zeeland’s central region.
Keywords: Factor analysis; Flood hazards; Netherlands; Social vulnerability index; Southwest Delta; Zeeland